«... la merdre n'était pas mauvaise»: Ubu roi – a Play for five Senses (Itinera, 2017)
Ubu roi of Alfred Jarry (1896) is known first and foremost as a revolutionary event in the history of modern theatre. However, before being a scandalous performance, Ubu roi is a grotesque puppet play that contains an infinite number of meanings and which appeals simultaneously to all five senses. The objective of this article is to examine Ubu roi from the point of view of its sensory evocations, and to demonstrate how this play reverts comically the symbolist search for correspondence of the senses.